The complexity of the relationship between human rights and national interests - Кudabayeva А.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The following article studies the complexity of relationships between the protection of human rights and national interest. National interest is an integral part of any states’ foreign policy. Although human rights and national interests are incompatible or even conflicting concepts, scholars argue that rights cannot be neglected and ought to play important role in states’ interests. The main purpose of the study was a thorough analysis of the tension between security and economic governmental interests and the defence of its citizens’ natural rights. The acuity of the issue is that quite often human rights are devalued due to the requirements of security or economy. The article raises the problem of the significance of international human rights and the necessity to protect a state basing its research on the theoretical framework of realism. As a result of the conducted research, it is possible to define the main factors constraining the protection of human rights.